(untitled) (Journal of Comparative Social Work, 2020)
This paper presents a brief history of the development of social work in Britain, exploring some of the tensions that derive from gaining public acceptance and social establishment. This is analysed using the psychoanalytic concepts of ambivalence and displacement. The locus that social work enjoys as part of the establishment is shown to be ambivalent. The establishment of social work as an accepted public face of welfare is critiqued, showing both the benefits of acceptance and problems that arise from seeking social approval. The positioning of contemporary social work as sacrifice will also be considered. It is in the role of ‘sacrifice’ that social work maintains its public face – carrying away the transgressions of society and being loaded with guilt by society (displacement) – but sacrifice also offers a way forward to maintain professional integrity by walking alongside the marginalised, disadvantaged, stigmatised and social work, offering itself as an expiation on behalf of the people with whom social workers practise